Efeito da terapia periodontal subgengival no controle glicêmico de pacientes com diabetes tipo 2: revisão sistemática e meta-análise de ensaios clínicos randomizados com 6 meses de acompanhamento - Oliveira, Victor Bento (2022)
The treatment of diabetes mellitus type 2 (T2DM) requires understanding of multiple metabolic pathways in order to maintain appropriate glycemic targets. Periodontal therapy is able to control the oral infection and reduce the systemic inflammatory burden, thus, many clinical trials investigated the potential effect of treating periodontitis on glycemic control. Previously, secondary studies summarized data about that topic, but there is still a need for clarification on the long-term effect of periodontal therapy (without the use of adjuvants) on glycemic control of patients with T2DM. This systematic review aims to answer the following question: Is subgingival periodontal therapy able to improve glycemic control by reducing glycated hemoglobin (HbA1c) levels in patients with T2DM compared to untreated diabetic patients after 6-months of follow-up? Nine electronic databases were accessed to collect primary information in the scientific literature without time restriction. The inclusion criteria were Randomized Controlled Clinical Trials (RCTs) with at least 6-months follow-up after subgingival therapy (scalling and root planing with or without open flap procedure), with periodontal status assessed by full mouth examination and a clear definition of periodontitis based on clinical and/or radiographic measures. The glycemic control should have been assessed by HbA1c. Studies written in non-Latin (Roman) alphabet and those that used systemic or local-delivery antimicrobial therapy were excluded. For meta-analysis, weighted mean differences (MDs) and 95% confidence intervals (CIs) were calculated for HbA1c. A total of 11 studies were included in the systematic review and 10 in meta-analyses (1324 patients). Subgingival therapy resulted in 0.24% lower HbA1c (WMD=0.24, 95%CI 0.06 – 0.41; p=0.01) compared to non-active periodontal treatment. The certainty in the body of evidence was assessed as moderate. The results of this study showed that subgingival periodontal therapy is associated with a significant improvement of glycemic control over six months in patients with T2DM and periodontitis.